2013
DOI: 10.1126/science.1236566
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Phosphorylation Sites Encode Their Sensitivity to Starvation and Rapamycin

Abstract: The mTOR Complex 1 (mTORC1) protein kinase promotes growth and is the target of rapamycin, a clinically useful drug that also prolongs lifespan in model organisms. A persistent mystery is why the phosphorylation of many bona fide mTORC1 substrates is resistant to rapamycin. We find that the in vitro kinase activity of mTORC1 toward peptides encompassing established phosphorylation sites varies widely and correlates strongly with the resistance of the sites to rapamycin as well as to nutrient and growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
394
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(432 citation statements)
references
References 50 publications
(77 reference statements)
25
394
3
Order By: Relevance
“…In contrast to the effective suppression of T-ALL progression by rapamycin, the cytostatic effect of rapamycin was not sufficient for the total eradication of T-ALL cells. The presence of rapamycin-insensitive mTORC1 substrates, like 4E-BP1, may account for this incomplete effect (13). Alternatively, the cytostatic effect of rapamycin on T-ALL may be mediated by mTORC2 inhibition because it was reported that Rictor deficiency significantly, but not completely, suppresses Notchdriven T-ALL (34), which is similar to the effect of rapamycin observed in our study.…”
Section: Inactivation Of Mtorc1 Prevents Oncogenic Kras-induced T-allsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast to the effective suppression of T-ALL progression by rapamycin, the cytostatic effect of rapamycin was not sufficient for the total eradication of T-ALL cells. The presence of rapamycin-insensitive mTORC1 substrates, like 4E-BP1, may account for this incomplete effect (13). Alternatively, the cytostatic effect of rapamycin on T-ALL may be mediated by mTORC2 inhibition because it was reported that Rictor deficiency significantly, but not completely, suppresses Notchdriven T-ALL (34), which is similar to the effect of rapamycin observed in our study.…”
Section: Inactivation Of Mtorc1 Prevents Oncogenic Kras-induced T-allsupporting
confidence: 78%
“…However, a study of conditional deletion of Rheb, which encodes an mTORC1 activator, or of mTOR with a Cd4-Cre transgene showed that mTORC1 inactivation does not result in apparent thymic phenotypes under steady-state conditions (12), leading to the possibility that rapamycin may affect T-cell development in an mTORC1-independent manner. In addition, it has been reported that 4E-BP1 is a rapamycininsensitive mTORC1 substrate, suggesting that rapamycin treatment does not necessarily represent mTORC1 inactivation (13).…”
mentioning
confidence: 99%
“…Interestingly, 2 studies aiming to characterize the mTOR phosphoproteome repertoire have identified LARP1 as a potential mTORC1 phosphorylation substrate. 74,75 This finding was recently corroborated using both in vitro and in vivo phosphorylation assays, 76 confirming LARP1 as a bona fide mTORC1 substrate. 77 Consistent with this, LARP1 was found to interact with the mTORC1-specific component Raptor, suggesting that LARP1 is an mTORC1-specific cell growth effector.…”
Section: Translational Control Of Top Mrnasmentioning
confidence: 49%
“…According to the gene ontology analysis, there are about 30 predicted amino acid permeases in the fission yeast genome. Half of these (49) are affected by ⌬isp7, either positively (3) or negatively (50) (see Tables S2 and S3 in the supplemental material). Interestingly, the amino acid permease aap1 ϩ , which we found as a multicopy suppressor of the sensitivity to rapamycin in tsc mutant cells, is downregulated in ⌬isp7 cells.…”
Section: Resultsmentioning
confidence: 99%